Duodenal volvulus of the sigmoid flexure in five cows. A retrospective study - Proios, I; Hoedemaker, M; Kiossis, E (Journal of the Hellenic Veterinary Medical Society, 2023)
Medical data of five Holstein Friesian cows with duodenal volvulus of the sigmoid flexure admitted to the Clinic for Cattle, University of Veterinary Medicine Hannover, Foundation, Hannover, Germany during a two-year period were reviewed in this study. The aim of this study was to present the clinical, laboratory and surgical findings as well as the postoperative healing progress and therapy of these five cases. All cows showed a loss of appetite and were dehydrated, with a marked drop in milk yield. The rumen motility was severely reduced and an untypical tympanic resonance or ping and a splashing sound were present at the right flank at auscultation. All the cows had only a small amount of faeces. All animals had hypochloraemic metabolic alkalosis and most of them hyperlactatemia. Two of the cows were hypokalaemic. Hyperbilirubinaemia was revealed in all cows. Four of the cows had an increased haematocrit level. A standing right flank laparotomy was performed in all cows. A common surgical finding was the severely dilated, dorsally dislocated and twisted sigmoid flexure of the duodenum, and the empty descending duodenum. The abomasum of all cows was dilated, but not displaced. An enlarged gall bladder was found in four animals. The duodenal sigmoid loop was manually untwisted, followed by promoting gas and ingesta flow aborally in the descending duodenum. Omentopexy was performed in each cow. No cow had had any history of omentopexy or other abdominal surgery. All cows received intravenous fluid therapy after the surgery. A total of 10-20 L 0.9 % NaCl solution containing an additional KCL (30 mmol/L) was administered intravenously via drip infusion daily for the first two days after surgery. Amoxicillin (10 mg/kg; s.c.) was administered once daily (SID) in two cases. Three of the cows were additionally drenched with 30 L water and 100-150 g KCL via an orogastric tube once per day for two days postoperatively. Four cows received neostigmine s.c. after surgery and for the following one to two days (every 8 or 12 hours; 0.02 mg/kg or 0.025 mg/kg, respectively). All cows were administered meloxicam (0.5 mg/kg; s.c.) before and on the first postoperative day. Sodium sulphate (250 g per os; SID) was administered to four cows for one to two days. Feed intake, rumen motility and defaecation were normalised gradually after surgery. All cows had a positive post-surgical outcome and were discharged from the clinic after 7 to 15 days. Keywords: ileus; dairy cattle; duodenum; intestinal obstruction